Encyclopedia of Colloid and Interface Science - Tadros, Tharwat (Springer Berlin Heidelberg : Imprint: Springer, 2013)
An authoritative and comprehensive reference relevant to all scientists and engineers in the field. This encyclopedia not only helps chemistry, materials science and physics researchers to understand the principles, but also provides practicing engineers with the necessary information for implementing practical applications, such as Food and agrochemicals Polymers and ceramics Cosmetics and detergents Paints and coatings Pharmaceuticals and drug delivery In addition, the encyclopedia is an important reference for industrial chemists and chemical engineers faced with a multitude of industrial systems of a colloidal nature. As wide as the range of applications that colloid and interface science has is the range of scientific disciplines that contribute to research and development in this field. These encompass chemistry, physics, biology and mathematics as well as nanoscience and nanotechnology. The encyclopedia provides easy-to-digest information for meeting these interdisciplinary challenges. While providing numerous concise definitions of key terms, the encyclopedia also features more than forty in-depth essays on topics ranging from Agrochemical Formulations to Zeta Potential. All entries are cross-referenced and include selected references to original literature as well as synonyms.